Taguchi-factorial type-2 fuzzy random optimization model for planning conjunctive water management with compound uncertainties. (November 2017) - Wang, C.X.; Li, Y.P.; Huang, G.H.
Abstract: In this study, a type-2 fuzzy random optimization (TFRO) method is developed for planning conjunctive water management system associated with compound uncertainties. TFRO can effectively address compound uncertainties expressed as type-2 fuzzy sets, probability distributions, and type-2 fuzzy random variables. Solution algorithm based on the degree of probability and the information of plausibility is proposed to transform nonlinear objective function and constraints into their linear equivalents. A real case of water-resources allocation problem in Zhangweinan River Basin (China) is employed to demonstrate the applicability of the proposed method. A Taguchi-factorial type-2 fuzzy random model is also formulated through introducing Taguchi design and ANOVA technique into the TFRO framework. Results obtained can help reveal the relationship among multiple impact factors of economic, environmental and resource (water conveyance efficiency, water delivery cost, and system violation risk), as well as quantify their contributions to the variability of system benefit and water allocation schemes. Highlights: A type-2 fuzzy random optimization (TFRO) method is proposed. It can tackle uncertainties expressed as type-2 fuzzy random variables. It is applied to Zhangweinan River Basin for conjunctive water management. A Taguchi-factorial type-2 fuzzy random optimization model is formulated. Parameter uncertainties and their interactions are analyzed in a systematic manner.